Intestinal Barrier Dysfunction in Fatty Liver Disease: Roles of Microbiota, Mucosal Immune System, and Bile Acids - Gupta, Biki; Rai, Ravi; Oertel, Michael; Raeman, Reben (Seminars in Liver Disease, 2022)
Nonalcoholic fatty liver disease (NAFLD) describes a spectrum of progressive liver diseases ranging from simple steatosis to steatohepatitis and fibrosis. Globally, NAFLD is the leading cause of morbidity and mortality associated with chronic liver disease, and NAFLD patients are at a higher risk of developing cirrhosis and hepatocellular carcinoma. While there is a consensus that inflammation plays a key role in promoting NAFLD progression, the underlying mechanisms are not well understood. Recent clinical and experimental evidence suggest that increased hepatic translocation of gut microbial antigens, secondary to diet-induced impairment of the intestinal barrier may be important in driving hepatic inflammation in NAFLD. Here, we briefly review various endogenous and exogenous factors influencing the intestinal barrier and present recent advances in our understanding of cellular and molecular mechanisms underlying intestinal barrier dysfunction in NAFLD.
Keywords: NAFLD; NASH; intestinal permeability; leaky gut; microbiome; bile acids; inflammation; mucosal immune cells